Physics of collisional plasmas introduction to high-frequency discharges - Moisan, Michel (Springer Netherlands, 2012)
The Physics of Collisional Plasmas deals with the plasma physics of interest to laboratory research and industrial applications, such as lighting, fabrication of microelectronics, destruction of greenhouse gases. Its emphasis is on explaining the physical mechanisms, rather than the detailed mathematical description and theoretical analysis. At the introductory level, it is important to convey the characteristic physical phenomena of plasmas, before addressing the ultimate formalism of kinetic theory, with its microscopic, statistical mechanics approach. To this aim, this text translates the physical phenomena into more tractable equations, using the hydrodynamic model; this considers the plasma as a fluid, in which the macroscopic physical parameters are the statistical averages of the microscopic (individual) parameters. This book is an introduction to the physics of collisional plasmas, as opposed to plasmas in space. It is intended for graduate students in physics and engineering . The first chapter introduces with progressively increasing detail, the fundamental concepts of plasma physic. The motion of individual charged particles in various configurations of electric and magnetic fields is detailed in the second chapter while the third chapter considers the collective motion of the plasma particles described according to a hydrodynamic model. The fourth chapter is most original in that it introduces a general approach to energy balance, valid for all types of discharges comprising direct current(DC) and high frequency (HF) discharges, including an applied static magnetic field. The basic concepts required in this fourth chapter have been progressively introduced in the previous chapters. The text is enriched with approx. 100 figures, and alphabetical index and 45 fully resolved problems. Mathematical and physical appendices provide complementary information or allow to go deeper in a given subject.